Climatic Hazards: High Importance but Low Severity to Coastal Rural Fishing Communities - Daniel Koomson; Katherine Sian Davies-Vollum; Debadayita Raha (Earth Science, Systems and Society)
This study examines the relative importance and severity of climate change in the context of multiple socio-economic stressors in rural coastal fishing communities in Ghana. Although climate change poses significant threats to these communities, it is yet unclear where it fits in the range of stressors that shape the vulnerability of such communities. Without an understanding of how vulnerability is experienced by the fishing communities, it is difficult to appreciate what adaptation to climate change means to them and which adaptation options are realistic. Household surveys, interviews, gender and age-group disaggregated focus group discussions and participatory risk mapping were used to assess type, importance and severity of climatic and socio-economic stressors that impinge on the lives and livelihood of the fishing communities. Climatic stressors include erratic rainfall, increased storminess, flooding and high temperatures. Socio-economic stressors include infrastructural (e.g., water and energy insecurity), socio-cultural (e.g., conflicts and land insecurity), occupational (e.g., exploitation, power asymmetries, illegal fishing), and environmental (e.g., plastic waste pollution) factors. The participatory risk maps showed that climatic stressors generally rank higher than all others in importance due to their direct impact on fishing and fish processing activities. However, socio-economic stressors were more severely felt, especially in major fishing seasons. The study therefore highlights socio-economic stressors as realistic focus for adaptation priorities that can safeguard the lives, livelihood and wellbeing of rural coastal-small scale fishing communities.